Stability analysis in terms of two measures for dynamic systems on time scales. (1993) - Kaymakçalan Kaymakçalan, Billûr Billûr
Abstract : Using the theory of Lyapunov's second method developed earlier for time scales, we extend our stability results to two measures which give rise to unification of several stability concepts in a single set up.